Tourism in the National Recovery and Resilience Plans of the EU member states - Sonia Mileva; Zlatina Lyutova (Eastern Journal of European Studies, 2023)
European Union member states have approached the tourism sector differently in the formulation of their respective National Recovery and Resilience Plans (NRRPs). An analysis of these plans has identified common themes, including digital and green transitions, sustainability, diversification of tourism offerings, and the development of workforce skills as integral components of strategic tourism development. Through a qualitative content analysis and comparative evaluation of all NRRPs, we assessed these plans based on three criteria: (1) Relevance to Tourism, (2) Support for Sustainable Tourism, and (3) Inclusion of Reform Components. This evaluation also highlighted the connections between NRRPs and the European Agenda for Tourism and the Transition Pathway for Tourism. The results indicate that NRRPs align with EU strategic priorities and effectively tackle country-specific challenges within the framework of the European Semester, underscoring the pivotal role of tourism in the EU's overall strategy.